The Religious Struggle Framework: Religious Experience from Struggle to Transformation - Nur Amali Aminnuddin (Islamic Guidance and Counseling Journal, 2022)
The phenomenon of young individuals struggling with their religious beliefs can lead to wide-ranging consequences. Existing studies are dominantly Western in context, which may not be applicable in other settings. Therefore, as contextualized and rationalized through an Islamic perspective, the present study aims to build a framework to explore religious struggle. Through a qualitative research design, multiple methods were employed: responses from six Muslim interviewees were reconstructed into a single monologue using the composite narrative method, and then narrative analysis was done, followed by method theory and domain theory analyses being conducted. Constructs were identified and discussed, theories as lenses to view the phenomenon were employed, and further evaluations of the phenomenon and relevant constructs were done. A discussion was integrated with each analysis. Through synthesizing the findings, I propose a framework called the religious struggle framework (RSF). With the RSF’s flexible, adaptable, and modifiable nature, the framework can be used beyond the present study’s population. It can be utilized in both quantitative and qualitative research designs. Limitations and recommendations for further research were also presented.